1993
DOI: 10.1111/j.1600-0722.1993.tb01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoride on caries progression and dentin apposition in rats fed on a cariogenic or non‐cariogenic diet

Abstract: The effect of fluoride in drinking water on the progression of dentinal caries and dentin apposition was studied in Wistar rats. The initiation of enamel caries lesions was first induced for 2 wk with S. sobrinus and a 43% sucrose diet after weaning. Thereafter the animals were fed on either a cariogenic or a non‐cariogenic diet and distilled water supplemented with 0, 1, 7 or 19 ppm fluoride. The areas of dentinal caries and dentin apposition were quantified after tetracycline staining. Fluoride reduced denti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We have also observed a negative correlation between the rate of dentin formation and dentinal caries progression in young rat molars (4). High (19 ppm) fluoride concentration in drinking water had an additional effect on the reduction of the dentin formation caused by the high sucrose diet (5). Fluoride also reduced dentinal caries progression (5).…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…We have also observed a negative correlation between the rate of dentin formation and dentinal caries progression in young rat molars (4). High (19 ppm) fluoride concentration in drinking water had an additional effect on the reduction of the dentin formation caused by the high sucrose diet (5). Fluoride also reduced dentinal caries progression (5).…”
mentioning
confidence: 50%
“…High (19 ppm) fluoride concentration in drinking water had an additional effect on the reduction of the dentin formation caused by the high sucrose diet (5). Fluoride also reduced dentinal caries progression (5). Thus, the possibility of a causal relationship between the increased caries progression in dentin and the decreased dentin formation is presently not clear.…”
mentioning
confidence: 99%
“…The number of more advanced dentinal caries lesions was higher in PHTmedicated rats than in controls, suggesting that PHT activated the rate of caries progression when caries had reached dentin ( Table 1). It has previously been found that fluoride in drinking water does not diminish the reducing effect of the high-sucrose diet on dentin apposition (19) but does reduce the rate of caries progression in dentin at concentrations of 1 and 19ppm. PHT worked the opposite way: it corrected the reducing effect of sucrose on dentin and increased the dentinal caries progression.…”
Section: Discussionmentioning
confidence: 98%
“…The Wistar rat has been frequently used in studies on caries. [32][33][34] Variations in pH, may lead demineralisation are dependant on the formation of a cariogenic dental plaque and on the conversion of sucrose in acids. The maintenance of the plaque is fundamental for the development of caries.…”
Section: Discussionmentioning
confidence: 99%